OPTIMASI PELAKSANAAN PROYEK KONSTRUKSI DENGAN METODE PERT DAN CPM - Hi. Muhammad, Amiruddin (Jurnal Ilmiah Ecosystem, 2017)
Implementation of a project work requires not only a reliable human resources, but also must be supported by a good management. Planning project activities is an issue that is very important because it is the basis for project planning in order to be able to finish the projects implemented with time and cost optimal. Method PERT and CPMis a management tool that is associated with the planning and control of costs and time on a project. Both of these methods can be applied in carrying out the project, so that all work can be run according to plan and provide more satisfactory results. The purpose of this study was to evaluate the time and cost Development Project Market Sarimalaha Tidore Islands, North Maluku. In searching for the possibility of achieving time a project that has been planned in the schedule with the analysis using PERT method and analyze the time and cost of the project through the acceleration of activity using CPM method. The data used data is market development project Sarimalaha Tidore Islands. From the research that has been carried out showed that that the possibility of the project is completed in accordance with the Time scedulle based analysis using PERT method amounted to 98.42%. For the analysis of acceleration events with CPM method showed that that the maximum acceleration of the process of acceleration occurs when the project can be accelerated up to 162,17 days from 170 days when the original plan and the cost of the project rose to Rp.8.857.795.386,00 of plan costs prior to acceleration is Rp.8,775,686,914.00. Thus a reduction in project time for 7,83 days and increase the cost of Rp.82.108.472,00at the time of reaching the maximum acceleration.